(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
In this article, the irrigated meadow-gray soils of the studied area with varying degrees of salinity are classified into groups according to their level of salinity. The types and degrees of soil salinization, as well as the causes and development of salinization, are examined. Measures aimed at improving and restoring the fertility status of soils that are difficult to reclaim are studied on the basis of scientifically grounded data, and relevant recommendations are provided.